2013
DOI: 10.3748/wjg.v19.i44.7947
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as tools to predict glucocorticoid response in inflammatory bowel diseases

Abstract: In spite of the introduction in therapy of highly effective biological agents, glucocorticoids (GCs) are still employed to induce remission in moderate to severe inflammatory bowel diseases (IBD), but considerable inter-individual differences in their efficacy and side effects have been reported. The effectiveness of these drugs is indeed very variable and side effects, particularly severe in pediatric patients, are common and often unpredictable: the understanding of the complex gene regulation mediated by GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It is evident that miRNAs could control also the expression of genes that are involved in drug response and therefore they could also play a role in Pharmacogenomics. Several studies have described the role of miRNA in drug response especially in cancer treatments in terms of drug resistance [18][19][20] but also in inflammatory bowel disease treatment [21]. Few studies have also described that polymorphisms in miRNA target regions could affect the expression of the genes and therefore the response to the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that miRNAs could control also the expression of genes that are involved in drug response and therefore they could also play a role in Pharmacogenomics. Several studies have described the role of miRNA in drug response especially in cancer treatments in terms of drug resistance [18][19][20] but also in inflammatory bowel disease treatment [21]. Few studies have also described that polymorphisms in miRNA target regions could affect the expression of the genes and therefore the response to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are a recently discovered class of small (19)(20)(21)(22)(23)(24) nucleotides) endogenous non-coding oligonucleotides that regulate gene expression at the post-transcriptional level [1][2][3]. They play a crucial role in regulation of physiological and pathological processes and some miRNAs have been described as associated with distinct clinical characteristics, such as diagnosis or disease activity [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…( De Iudicibus et al 2013). In the present study, we did not explore whether GR was involved in the regulation of miR199a-5p by GCs in osteoblasts.…”
Section: Discussionmentioning
confidence: 76%
“…Results described in several recent reports have indicated that GCs exert post-transcriptional control through the regulation of miRNA processing and expression (De Iudicibus et al 2013). Xing et al (2014) reported that GCs induced apoptosis by inhibiting miRNA cluster miR-17-92 expression in chondrocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they found that MiR-31 expression levels increased with disease progression and accurately discriminated neoplastic from normal or chronically inflamed tissues in IBD patients. miRNAs might also be used as tools in predicting or assessing response to therapy, as miRNA levels before and after glucocorticoid (GC) treatment appeared to be significantly different [159]. In addition, when serum samples of 19 patients receiving IFX induction therapy were analyzed, miRNA levels of let-7d and let-7e were significantly increased in the clinical remission group [160].…”
Section: Microrna Biomarkersmentioning
confidence: 99%